"I break and bend". Posture, lifts and musculoskeletal disorders among preschool teachers - Sottimano, Ilaria; Viotti, Sara; Guidetti, Gloria; Cascio, Vincenza; Converso, Daniela (La Medicina del Lavoro, 2018)
Background: Nursery school teachers are subjected to unavoidable physical demands, such as picking up children, putting them in the cradle, changing diapers etc. The potential detrimental effects on the workers’ musculoskeletal system are amplified by the aging of the working population observed in recent years. Objectives: To describe the psychophysical health of nursery school teachers employed in a North-Western Italy municipality and their age-related problems. Methods: Data were collected through a medical examination for the identification of musculoskeletal disorders, and a contextual self-administered questionnaire (for the identification of: awkward postures, work ability and depression). Results: Nursery school teachers often adopt awkward positions during their working day, mainly lifting (93.6%) and squatting position (61.1%). Perceived musculoskeletal pain is common, especially cervical pain (63.3%) and lumbosacral pain (67.5%). Working ability was found to be good or mediocre, and inversely related with age. Depression had a fairly low prevalence (2%). Conclusions: Findings highlight some critical issues inherent to the working conditions of nursery school teachers, underlining the need to introduce preventive measures that, in order to effectively support workers, should be adopted starting from the beginning of their career.